Correction of hallux valgus and forefoot alignment based on the Chevron, Akin and Weil techniques - Paula, Sidney Silva de; Klein Júnior, Afonso; Sakamoto, Yugo Willian; Mariúba, Eduardo Sávio de Oliveira; Assis, Peterson Souza de; Secco, Wesley Guidi (Scientific Journal of the Foot & Ankle, 2018)
Objective: To perform an evaluation, based on the 36-Item Short Form Health Survey (SF-36) quality of life questionnaire and American Orthopedic Foot and Ankle Score (AOFAS), of the clinical outcome of patients with a diagnosis of hallux valgus and with hallux and lesser toes surgically treated using the Chevron, Akin and Weil techniques. Methods: Eleven patients with a diagnosis of hallux valgus, treated using the aforementioned techniques between January 2005 and December 2009 and with a minimum follow-up of 24 months, were evaluated. All patients completed the SF-36 and AOFAS questionnaires for the hallux and lesser toes. Results: According to the SF-36, nine patients had good general health, six performed all types of physical activities, six had no problems with physical activities, six had no problems as a result of emotional aspects, eight performed their normal social activities, seven had no pain or limitation of activities due to pain, seven felt excited and full of energy, and seven felt at peace, happy and calm. According to the AOFAS, six good and excellent results were obtained for the lesser toes, and eight good and excellent results were obtained for the hallux. The only significant difference observed in the SF-36 score was for Vitality and Mental Health in patients over 60 years of age, and no differences were observed in regard to patient gender. No differences were observed between age groups or genders in regard to the AOFAS. Conclusion: According to the SF-36 and AOFAS, the combined techniques achieved good results and are therefore recommended for the treatment of hallux valgus and foot alignment. Level of Evidence III; Retrospective Comparative Study.